Linaclotide utilization and potential for off-label use and misuse in three European countries - Cid-Ruzafa, Javier; Lacy, Brian E.; Schultze, Anna; Duong, Mai; Lu, Yi; Raluy-Callado, Mireia; Donaldson, Robert; Weissman, Darren; Gómez-Lumbreras, Ainhoa; Ouchi, Dan; Giner-Soriano, Maria; Morros, Rosa; et al. (Therapeutic advances in gastroenterology, 2022)
Introduction: Linaclotide is approved for adults with moderate-to-severe irritable bowel syndrome (IBS) with constipation (IBS-C). Linaclotide is not indicated for weight loss or for patients with inflammatory bowel disease (IBD); it is contraindicated in patients with mechanical bowel obstruction (MBO). Some patients with obesity or eating disorders (ED) may use linaclotide off-label for weight loss or as a laxative. Objectives: To describe the use of linaclotide in clinical practice, including patients with potential for off-label use or misuse. Methods: Post-authorization safety study conducted in three databases from the linaclotide launch date to 2017: the Clinical Practice Research Datalink in the United Kingdom (UK), the Information System for Research in Primary Care database in Spain and the linked Patient, Prescription and Causes of Death Registries in Sweden. Cohorts of patients were identified as having IBS using diagnostic and treatment codes; IBS subtypes were identified using symptoms and treatment codes; patients with obesity, ED, MBO, and IBD were identified using diagnostic codes or body mass index. Results: There were 1319, 1981, and 5081 linaclotide users from the United Kingdom, Spain, and Sweden with a median age of 45, 57, and 51 years, respectively; most were females. In the United Kingdom, Spain, and Sweden, respectively: 59.0%, 60.3%, and 31.3% of linaclotide users had an IBS diagnosis recorded, and among those, 68.8%, 61.3%, and 92.7% were classified as IBS-C. The proportions of linaclotide users considered at risk for potential off-label use for weight loss or as a laxative were 17.1%, 29.7%, and 1.7%, and the proportions of users considered at risk of misuse due to a history of MBO or IBD were 3.5%, 4.6%, and 5.7% in the United Kingdom, Spain, and Sweden, respectively. Conclusions: Potential linaclotide off-label use and misuse appears limited, as evidenced by the small sizes of the patient subgroups at risk for off-label use and misuse.